Circular RNA Circ_0067934 Attenuates Ferroptosis of Thyroid Cancer Cells by miR-545-3p/SLC7A11 Signaling - Wang, Hui-Hui; Ma, Jia-Ni; Zhan, Xiao-Rong (Frontiers in Endocrinology, 2021)
Ferroptosis is an emerging programmed cell death distinguished from apoptosis and autophagy and plays essential roles in tumorigenesis. Thyroid cancer is a prevalent endocrine tumor, but the molecular mechanism of ferroptosis during thyroid cancer development remains unclear. Here, we identified the critical function of circular RNA circ_0067934 in repressing ferroptosis of thyroid cancer cells. Our data showed that the ferroptosis activator erastin decreased thyroid cancer cell viabilities, while the circ_0067934 shRNA further attenuated erastin-inhibited cell viabilities. The silencing of circ_0067934 enhanced the levels of ferroptosis-related markers, including Fe2+, iron, and ROS in the cells. The knockdown of circ_0067934 induced thyroid cancer cell apoptosis and repressed thyroid cancer cell proliferation in vitro and in vivo. Circ_0067934 upregulated the expression of the ferroptosis-negative regulator SLC7A11 by sponging and inhibiting miR-545-3p in thyroid cancer cells. The overexpression of SLC7A11 or the inhibitor of miR-545-3p reversed circ_0067934 silencing-regulated thyroid cancer cell proliferation. Therefore, we concluded that Circ_0067934 attenuated ferroptosis of thyroid cancer cells by miR-545-3p/SLC7A11 signaling. Circ_0067934 may serve as a potential therapeutic target by regulating ferroptosis for the treatment of thyroid cancer.